INTEGRASI PENDIDIKAN KARAKTER DI SMP PONDOK PESANTREN MODERN NURUL IKHLAS KABUPATEN TANAH DATAR SUMATERA BARAT - Hadiyanto Hadiyanto (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
The study of integration of character education in Junior Secondary School Nurul Ikhlas Tanah Datar, West Sumatra is a joint research with the approach of a combination of quantitative and qualitative, aims to understand the efforts undertaken by the leadership of the boarding school and the principal to integrate character education or character values that are universal to the school management processes. Among the character values uniquely invested in modern boarding school Nurul Ikhlas are: Deepening Religious Sciences, the mole, Compliance, Modeling, Piety, Independence, Discipline, Simplicity, Tolerance, feel enough, Humility, Fortitude, Solidarity, Sincerity, Cling to religion, Society, Cleanliness. The seventeenth character is jointly invested well for students to learn at school and when students receive education from boarding schools, to teachers and other education personnel. The uniqueness of Junior Secondary Boarding School Nurul Ikhlas in integrating character education into the educational process so as to produce quality graduates, an attraction for parents and prospective students to study at the boarding school. This concern which contribute optimally to support both leaders and the head of the boarding school so that the educational process can be managed optimally. This suggests the process of character education is not only optimal in boarding schools, but also in regular schools, both public and private that currently require it.